USSR : detente, handel en dissidenten - van den Berghe, Francis; Durieux, Hugo; Esch, Toon; Lowette, Toon; Mertens, Ludo (Berchem : EPO, 1980)
De grote vraag die in dit boek wordt gesteld: gaan we terug naar een nieuwe koude oorlog?